Design and analysis of DOE-based microinterferometer - Jozwik, Michal; Wielgo, Krzysztof; Kozacki, Tomasz (Photonics Letters of Poland, 2011)
This paper describes the design and numerical study of a Twyman-Green microinterferometer based on Diffractive Optical Elements (DOEs). Its compact design allows to fabricate several interferometers in an array-like pattern on an optical wafer - with horizontal dimensions appropriately adapted to the tested structures. To prove the design concept of the proposed interferometer configuration a laboratory setup was realized. The first results of the interferometric measurements on an MEMS object are presented. Full Text: PDF References: http://www.ict-smartiehs.eu [DirectLink] M. Kujawinska et al., "Design, technology, and signal processing for DOE-based microinterferometer array applied in new generation M(O)EMS test equipment", Proc. SPIE 7791, 779103 (2010).[CrossRef] T. Kozacki et al., "Reconstruction of refractive-index distribution in off-axis digital holography optical diffraction tomographic system", Opt. Exp. 17, 13758 (2006). [CrossRef] B. Kim et al., "Scanning Grating Microinterferometer for MEMS Metrology", J. Manuf. Sci. Eng. 126, 807 (2004). [CrossRef] R.C. Rumpf, PhD Thesis, College of Optics / CREOL&FPCE (2006). M.G. Moharam et al., "Formulation for stable and efficient implementation of the rigorous coupled-wave analysis of binary gratings", J. Opt. Soc. Am. A 12, 1068 (1995). [CrossRef] P. Lalanne, M. Morris, "Highly improved convergence of the coupled-wave method for TM polarization", J. Opt. Soc. Am. A 13, 779 (1996). [CrossRef] V.A. Soifer, Methods for computer design of diffractive optical elements (New York, John Wiley & Sons 2002). D. Dias et al., "High-frequency gratings for applications to DVD pickup systems", J. Opt. A 3(3), 164 (2001). [CrossRef]